PENERAPAN PEMBERIAN TERAPI MUSIK RELIGI “DEMI MASA” UNTUK PENURUNAN TINGKAT KECEMASAN PASIEN PRE OPERASI DENGAN REGIONAL ANASTESI SUB ARACHNOID BLOK DI RUMAH SAKIT K.R.M.T WONGSONEGORO SEMARANG - Ns. Ainnur Rahmanti; Rani Pratiwi (Pusat Riset dan Inovasi Nasional, 2021)
Anxiety is a normal adaptive response to stress due to surgery. Anxiety caused by fear of pain, fear of physical changes and not functioning normally after surgery, one of the ways to overcome it is with relaxation and distraction techniques, namely with religious music therapy. The purpose of this case study was to describe the application of religious music therapy